Asistensi Mahasiswa Dalam Penanganan dan Penyelesaian Kasus Kejahatan Jalanan Remaja ‘Klitih’ di Satuan Kepolisian : Studi Polresta Sleman Polda D.I. Yogyakarta - Prisgunanto, Ilham (Jurnal Pengabdian Kepada Masyarakat Kalam, 2024)
Street crimes are increasingly rampant and dangerous, especially in Yogyakarta Regional Police, which is known as Klitih, which is different from the real meaning. Klitih crimes often occur at night and the perpetrators are mostly teenagers. This street crime is quite troubling because it will disturb the security and order of the environment which has an impact on economic development in the region. This community service activity was carried out by STIK Lemdiklat Polri by going directly to Polda D.I. Yogyakarta with a study of Sleman Police. The theoretical studies used in this community service are Karl Marx's alienation theory, social conflict and law enforcement. This community activity was carried out using assistance techniques and FGD (Focus Group Discussion) to the Yogyakarta Police, members of Sleman Police and STIK Lemdikpol students. The results of the community service showed that the Klitih crime arose because of the alienation of teenagers in the face of the tourist industry in Yogyakarta. This causes them to be left out and run away in the form of showing off to the environment about their existence. Therefore, all parties must understand this by eliminating the social gaps that exist in today's youth. Handling this crime case must involve parents and all parties as a strict social control in order to realize security and order.